India Foundation for Education Transformation: Its Service to the Society - Mandal, Ranjit Kumar; Chakma, Sanjoy (Journal of Advanced Research in English & Education, 2021)
Skill is the most important component in education which makes a person capable of earning his or her livelihood. The system of education takes care of the development of school skills among the children in the schools. But the spread of pandemic Covid-19 has drastically disrupted every aspects of human life including education and impacted the skill development process has also been impacted. It has created an unprecedented test on education. Outbreak of COVID-19 has impacted more than 120 crores of students and youths across the planet. In India, more than 32 crores of students have been affected by the various restrictions and the nationwide lockdown for COVID-19. In many educational institutions around the world, campuses are closed, and teaching-learning has moved online. In India many schools were quick to react but to a limited extend. While many schools in the cities have adapted to online teaching schools in the remotest areas did not have the resources to get on the starting grid. Here the India Foundation for Education Transformation moved in a contributed its bit. How to cite this article:  Mandal RK, Chakma S. India Foundation for Education Transformation: Its Service to the Society. J Adv Res Eng & Edu 2020; 5(3): 9-11. DOI: https://doi.org/10.24321/2456.4370.202011